2000
DOI: 10.1054/bjoc.2000.1324
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen inactivation in the colon: analysis of the expression and regulation of 17 β -hydroxysteroid dehydrogenase isozymes in normal colon and colonic cancer

Abstract: Summary Epidemiological data suggest that oestrogen contributes to the aetiology of colonic cancer. Furthermore, recent studies have suggested that local hormone metabolism may play a key role in determining colonic responsiveness to oestrogen. To further clarify this mechanism we have characterized the expression and regulation of isozymes of 17β-hydroxysteroid dehydrogenase (17β-HSD) in vitro and in situ. Immunohistochemistry was used to confirm expression of the type 2 and 4 isozymes of 17β-HSD (17β-HSD2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Based on Northern analysis, they concluded that the decrease was due mainly to decreased expression of 17HSD type 4, another 17HSD enzyme with oxidative activity. In another report, 29 it was suggested that both 17HSD types 2 and 4 isozymes were abnormally expressed in colon tumors, as assessed by immunohistochemistry. Our previous studies with several cell lines originating from various tissues have shown, however, that the 17HSD activity of the type 4 enzyme is very low and that there is no correlation between 17HSD type 4 mRNA expression and 17HSD activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on Northern analysis, they concluded that the decrease was due mainly to decreased expression of 17HSD type 4, another 17HSD enzyme with oxidative activity. In another report, 29 it was suggested that both 17HSD types 2 and 4 isozymes were abnormally expressed in colon tumors, as assessed by immunohistochemistry. Our previous studies with several cell lines originating from various tissues have shown, however, that the 17HSD activity of the type 4 enzyme is very low and that there is no correlation between 17HSD type 4 mRNA expression and 17HSD activity.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism of the protective effect is not clear; however, inhibition of cell proliferation by E1 has been described. 28,29 This might provide one of the mechanisms whereby E1 administered in HRT could reduce coloncancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of sex steroid receptors in human colorectal cancers was shown a long time ago (18,19) and confirmed by more recent studies (20,22). Some studies suggest that oral contraceptives and hormonal replacement therapy may decrease the risk of colorectal cancer (23,24), but there are conflicting reports whether estrogen receptors and estrogens have a protective effect against colon carcinoma or a stimulatory action (22,25).…”
Section: Introductionmentioning
confidence: 99%
“…To date, some studies already investigated mRNA expression of sex steroid biosynthesis enzymes in different androgen-dependent tissues from healthy humans and also from patients with different diseases [English et al, 2000;Kim et al, 2002;Provost et al, 2002;Blouin et al, 2003;Labrie et al, 2003;Oduwole et al, 2003;Oliveira et al, 2003;Quinkler et al, 2003Quinkler et al, , 2004Stoffel-Wagner, 2003]. This includes reproductive dysfunction and polycystic ovary syndrome (PCOS) and also various malignancies [Koh et al, 2002;Gunnarsson et al, 2003;Labrie et al, 2003;Vihko et al, 2003].…”
mentioning
confidence: 99%